Feelings Related to the Academic Path in Virtue of the COVID-19 Pandemic: Testimonies from Portuguese Higher Education Students Attending Healthcare Courses - Minghelli, Beatriz; De Oliveira Tavares, Elsy Alejandra; De Sousa Frango Pinheiro, Maria Teresa (European Journal of Mental Health, 2022)
Introduction: In Portugal, two periods of confinement were implemented due to the COVID-19 pandemic (i.e., March 2020, January 2021), and closing the educational institutions was one of the containment measures adopted. Medical students felt the impact of these confinement periods because healthcare education has a very high practical component in the context of clinical teaching: it is impossible to teach these healthcare disciplines via distance learning methodology. Aims: This study aims to identify the feelings related to the academic path in higher education students attending healthcare courses as a consequence of confinement. Methods: The sample included 133 students, aged between 18 and 55 years, 77 (68.1%) were female. This was a qualitative and cross-sectional study using a content analysis approach. The measurement instrument included an online questionnaire. Results: From the results, demotivation, anxiety, insecurity and fear of being contaminated stand out as the most present and reported student feelings. All these new feelings led to a shift in the mental health status, which most students currently classify negatively as a result of all the changes ex-perienced during this time. Most students expressed negative feelings resulting from the pandemic, asserting that confinement interfered with their academic path in a negative way regarding their mental health. Conclusions: The decrease in practical classes led to a feeling of insecurity and fear in patient care. It is suggested that the mental health of university students be monitored during epidemics in order to try to minimize the impacts caused on their mental health.